Empathy in leadership: a systematic literature review on the effects of empathetic leaders in organizations - Caroline Muss; Dana Tüxen; Bärbel Fürstenau (Management Review Quarterly, 2025)
Numerous studies have examined the impact of empathetic leaders in organizations. However, the systematic consolidation and categorization of these effects have not yet been conducted. This article presents a systematic literature review of 42 academic studies, carefully selected from 5 databases using a rigorous search process, with the aim of developing a concise category system that synthesizes the effects of empathetic leaders in organizations. After discussing theoretical lenses and our methodological approach, we outline the various understandings of empathy and the measuring instruments used in the analyzed articles. As our main contribution, we then describe nine categories that summarize the effects of empathetic leaders in organizations. These categories consider affect, attitudes, empathy, equity, interpersonal relationships, leadership practice, perception, performance, and well-being. We further outline the individuals or groups affected by these effects. Finally, we discuss our results and offer future research avenues for the scientific community as well as practical recommendations for three different stakeholders who can shape empathetic leadership in organizations: leaders, human resources (HR) managers, and board members.
Keywords: M10; M12; 650; Empathy; Leadership; Empathetic leaders; Effects; Categorization; Systematic literature review